Characterizations of GaN-based high-electron-mobility-transistors (hemts) - Wong, Wei Jie. (2012)
Studies on the characteristics of AlGaN/GaN high-electron-mobility transistor (HEMTs) were performed based on the interest of understanding and evaluation of the device performance. This report will focus on the studies of drain current collapse issue on the GaN based HEMTs under the influence of different temperature, surface passivation layer with the variation of gate-to-drain spacing (LGD) and the effect of drain quiescent-bias (VDS0). To understand the origin of drain current collapse, the